(untitled) (Bangladesh Journal of Botany, 2020)
Staining property of interphase nuclei and prophase chromosomes, diploid chromosome number, total chromosome length (TCL), symmetric and asymmetric indices of karyotype were studied in eight maize varieties released by BARI. 2n = 20 chromosomes were found in Barnali, Mohor, Khoi Vhutta, BS-1, B-5 and BM-7 whereas 2n = 22 chromosomes in China and 2n = 24 chromosomes in B-73 were observed. TCL was highest in Mohor (190.49 ± 5.61 μm) and lowest in B-73 (69.30 ± 2.51 μm). These varieties showed significant variation in cytogenetical parameters. Results obtained are expected to supplement genetic identification of maize varieties in variety conservation efforts.